2015
DOI: 10.1126/science.aaa4535
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the CRISPR-Cmr complex reveal mode of RNA target positioning

Abstract: Adaptive immunity in bacteria involves RNA-guided surveillance complexes that use CRISPR (clustered regularly interspaced short palindromic repeats)-associated (Cas) proteins together with CRISPR RNAs (crRNAs) to target invasive nucleic acids for degradation. While Type I and Type II CRISPR-Cas surveillance complexes target double-stranded DNA, Type III complexes target single-stranded RNA. Near-atomic resolution cryo-electron microscopy (cryo-EM) reconstructions of native Type III Cmr (CRISPR RAMP module) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(183 citation statements)
references
References 29 publications
(22 reference statements)
17
144
0
Order By: Relevance
“…The interaction of the Cmr complex with target RNA is guided by crRNA/target RNA complementary base-pairing (Hale et al 2009(Hale et al , 2012Ramia et al 2014). Multiple Cmr4 subunits, which form the backbone of the complex, mediate cleavage of the bound target RNA at regular 6-nt intervals (Staals et al 2013;Benda et al 2014;Hale et al 2014;Ramia et al 2014;Taylor et al 2015). Recent data indicate that the Cmr system of Sulfolobus islandicus is capable of transcription-dependent, plasmid silencing in vivo, although this activity has not been recreated with purified components or characterized in detail (Deng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of the Cmr complex with target RNA is guided by crRNA/target RNA complementary base-pairing (Hale et al 2009(Hale et al , 2012Ramia et al 2014). Multiple Cmr4 subunits, which form the backbone of the complex, mediate cleavage of the bound target RNA at regular 6-nt intervals (Staals et al 2013;Benda et al 2014;Hale et al 2014;Ramia et al 2014;Taylor et al 2015). Recent data indicate that the Cmr system of Sulfolobus islandicus is capable of transcription-dependent, plasmid silencing in vivo, although this activity has not been recreated with purified components or characterized in detail (Deng et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This allows sharing of crRNA processing pathways, with the mature crRNAs ultimately getting loaded onto specific effector complex. Type III system displays two kinds of effector complexes -Csm (Type III-A/D) or Cmr (Type III-B/C) (Hale et al, 2009;Zhang et al, 2012; Hatoum-Aslan et al, 2013;Rouillon et al, 2013;Tamulaitis et al, 2014;Zhang et al, 2016), which show distant relationship with Type I effector complex (Rouillon et al, 2013;Osawa et al, 2015;Taylor et al, 2015).…”
Section: Type I and Type Iii Crispr Systemsmentioning
confidence: 99%
“…However, in case of type III systems, pre-CRISPR transcript is processed by Cas6 in solitude and not as part of the effector complex (Carte et al, 2008; Carte et al, 2010;Wang et al, 2011;Shao and Li, 2013;Shao et al, 2016; Makarova et al, 2017a). Further, Cas6/III does not become a constituent of interference complex (Hale et al, 2009;Zhang et al, 2012;Rouillon et al, 2013;Spilman et al, 2013; Benda et al, 2014;Staals et al, 2014;Osawa et al, 2015;Taylor et al, 2015; Makarova et al., 2017a), with the exception being Csm/III-A complex from Streptococcus thermophilus that shows weak transient interactions with Cas6 (Tamulaitis et al, 2014). This possibly grants Cas6/ III the flexibility required to associate with multiple subtypes that potentially differ at the interference stage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the last five years, we've been working on CRISPR/Cas9 complexes," says Nogales. Most recently, their studies revealed how thumb-like subunits of the CRISPR-Cmr complex extend into the target RNA and facilitate its cleavage (10). In 2012, Nogales and biochemist Andreas Martin, whom she had convinced of cryo-EM's applicability to his study of proteosomes, published the structure of more than 30 subunits of the yeast 26S proteasome, revealing the mechanistic underpinnings of ubiquitin-dependent protein degradation (11).…”
Section: High Resolutionsmentioning
confidence: 99%